Transgressions: critical Australian Indigenous histories - Macfarlane, Ingereth (Aboriginal History Monograph, 2007)
This volume brings together an innovative set of readings of complex interactions between Australian Aboriginal people and colonisers. The underlying theme is that of 'transgression', and Michel Foucault's account of the necessary dynamic that exists between transgression and limit. We know what constitutes the limit, not by tracing or re-stating the boundaries, but by crossing over them. By exploring the mechanisms by which limits are set and maintained, unexamined cultural assumptions and dominant ideas are illuminated. We see the expectations and the structures that inform and support them revealed, often as they unravel. Such illuminations and revelations are at the core of the Australian Indigenous histories presented in this collection.